Digital Risk Management Strategies for Navigating Indonesia's Banking Digital Transformation: A Case Study of Himbara (Bank XYZ) - Fajar Guna Ma’sum; Yudho Giri Sucahyo (Glosains: Jurnal Sains Global Indonesia, 2026)
Background: Digital transformation has enhanced efficiency in Indonesia’s banking industry while creating increasingly complex digital risk challenges. This study examines the digital risk management strategy implemented by Bank XYZ, focusing on the absence of a comprehensive risk management framework and the inadequate fulfillment of internal and external requirements. Objective: This study aims to analyze gaps in Bank XYZ’s digital risk management practices and develop an integrated strategy based on the People, Process, Technology, and Organization (PPTO) framework, incorporating ISO 31000:2018 and COBIT 2019 to support sustainable digital transformation. Methods: This research adopts the ISO 31000:2018 framework, COBIT 2019, and digital risk theory, integrating risk management principles with the People, Process, Technology, and Organization (PPTO) approach. The study employs an applied research methodology using qualitative data obtained from interviews with key informants, internal data from Bank XYZ, regulatory documents, and industry best practices. Results:  The findings indicate that while Bank XYZ has established digital risk management strategies, their implementation and adequacy remain suboptimal. Strategic recommendations were developed based on risk analysis and Focus Group Discussion (FGD) results, utilizing ISO 31000:2018 and COBIT 2019 frameworks across four primary areas: strengthening human resources and digital risk culture, optimizing business processes, enhancing the automation and integration of risk monitoring systems, and improving digital risk governance at the organizational level. Conclusion: The study concludes that the success of digital risk management at Bank XYZ is highly dependent on the consistency of implementation across all organizational levels and the institution’s readiness to adapt to the evolving risk landscape in the digital era.